Electronic Word of Mouth (E-WOM) and Consumer Trust as Determinants of Online Purchase Decisions among Millennial Mothers on Shopee Marketplace - Putri, Deasy Soraya A. Aminartha; Arfianty (MANDAR: Management Development and Applied Research Journal, 2025)
The rapid development of digital technology has significantly transformed consumer behavior, particularly in purchasing decisions made through e-commerce platforms. Among various digital marketing tools, electronic word of mouth (e-WOM) has emerged as one of the most influential sources of information shaping online consumer behavior. This conceptual paper aims to examine the theoretical relationship between e-WOM and consumer trust in influencing online purchase decisions on Shopee, particularly among millennial mothers. Using a descriptive-analytical and literature-based approach, this study reviews relevant empirical research and theoretical discussions published between 2019 and 2024. The analysis reveals that e-WOM positively influences both consumer trust and purchase decisions, while trust serves as a crucial mediating factor that strengthens the impact of e-WOM. The findings emphasize that authentic testimonials and digital trust are essential strategies for developing sustainable consumer engagement and purchasing confidence in today's experience-based digital economy